If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2y = 36 Solving 9x + 2y = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 9x + 2y + -2y = 36 + -2y Combine like terms: 2y + -2y = 0 9x + 0 = 36 + -2y 9x = 36 + -2y Divide each side by '9'. x = 4 + -0.2222222222y Simplifying x = 4 + -0.2222222222y
| 4t^2-3t-5=0 | | -8x-7x=64 | | 5x-10+5x=-10 | | 5x-3=3x-11 | | -3x-7y=21 | | x+x^2=x^3 | | (9-2x)2=0 | | 8y+9x=36 | | -3x+5=11 | | 0.5(x+2)=0.1+3(0.1+0.3) | | in(7x+4)=1 | | 1/4+1/13-1/52 | | 2x/3y^2.6y/4x | | 2x/3y2.6y/4x | | x*5=84 | | 81x^2+16=0 | | 3+4x+x^4=0 | | 16u^2+16u-5=0 | | (4t-23)(t+5)=-110 | | 4x2/3=34/3 | | t^2=1t | | 55+55= | | -4(x+8)-45=6-55 | | 22x+8-25x=1-5 | | x-6=10/5 | | 3u^2-16u+5=0 | | u^2-16u+5=0 | | 3x^4+12x+9=0 | | 10(12c+8)= | | x^2+15=2-6x | | (y^2)*(y-1)=48 | | 12+0+11+1= |